Chemical Heterogeneity of Metal Oxide Surfaces as Studied by Inverse Gas Chromatography at Finite Concentrations - V.I. Bogillo; V.P. Shkilev; A. Voelkel (Adsorption Science & Technology)
A method for the calculation of the heterogeneous solid surface distribution function on the adsorption (free adsorption) energy as the sum of two uniform functions and on parameters describing the donor–acceptor and dispersive properties of the adsorption sites direct from chromatographic peaks as measured by inverse gas chromatography of ‘test ’ adsorbates at finite concentrations has been proposed. Average parameters reflecting the donor–acceptor properties of the adsorption sites and the dispersive component of the free surface energy in the monolayer region for the individual and mixed Si, Ti and Al pyrogenic oxide surfaces were determined using this method from the adsorption data for 18 ‘test ’ compounds possessing different donor–acceptor and polarizable properties.